An assessment of emergency department information systems based on the HL7 functional profile - Sakineh Saghaeiannejad-Isfahani; Farzaneh Hazhir; Reza Jalali (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: Emergency Department Information System (EDIS) plays a significant role in supporting the emergency department (ED) workflow. Hence, it is vital to assess the services provided by this system in order to identify its strengths and weaknesses. AIMS: The study aimed to assess the information systems in use in the ED of 11 teaching hospitals associated with Isfahan University of Medical Sciences (IUMS) so as to identify their strengths and weaknesses and improving the quality of these systems. SETTINGS AND DESIGN: This study was conducted using descriptive-applied research method. SUBJECTS AND METHODS: Data collection tool was a checklist developed based on EDIS functional profile. It covered two sections of the profile, namely direct care and supportive functions and their respective subsections. STATISTICAL ANALYSIS USED: Data were analyzed using descriptive statistics through the estimation of the frequency and frequency percentage for each respective section and subsections using SPSS software v. 20. RESULTS: The content conformance rate of the information systems in use in the EDs of IUMS' teaching hospitals was found to be 49.72% and 75.25% for the direct care section and supportive functions section, respectively. In addition, the overall conformance rate in the hospitals surveyed was up to 53.15%. CONCLUSION: As per the findings of this study, it is suggested that some important clinical and administrative functions should be incorporated into the redesigned information systems in use in the EDs under study.